KONSEP POLIGAMI MENURUT OEMAR BAKRY: (Studi Kajian Penafsiran Tafsir Rahmat) - Rahayu, Fitri; Sartika, Ela (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2024)
This research is motivated by the widespread public response to polygamists, both for and against, with various views. Therefore, this research focuses on studying Oemar Bakry in interpreting verses that relate to polygamy in Tafsir Rahmat. Modern thinking and scientific approaches make Oemar Bakry have a different view in studying polygamy verses. This research uses a qualitative method approach library research. This research resulted in the conclusion that Oemar Bakry considers that the text which implicitly allows polygamy cannot be removed or abolished but requires a re-examination of the verse. So, according to Oemar Bakry, polygamy is used as an emergency exit which can be used in case of emergency. Second, the practice of polygamy must be based on justice both physically and spiritually, which is the main requirement, although it is adjusted to the abilities of the polygamist (husband). Third, must be connected mu'asyarah bil ma'ruf in marriage. Fourth, every problem needs to find a solution and the last resort is divorce if the problem cannot be fixed. Therefore, the ideal marriage according to Oemar Bakry is a monogamous marriage.